2005
DOI: 10.1007/s00439-005-0063-3
|View full text |Cite
|
Sign up to set email alerts
|

A new locus (RP31) for autosomal dominant retinitis pigmentosa maps to chromosome 9p

Abstract: Retinitis pigmentosa (RP) is a debilitating disease of the retina affecting approximately 1.5 million people worldwide. RP shows remarkable heterogeneity both clinically and genetically, with more than 40 genetic loci implicated, 12 of which account for the autosomal dominant form (adRP) of inheritance. We have recently identified a French Canadian family that presents with early onset adRP. After exclusion of all known loci for adRP, a genome-wide search established firm linkage with a marker from the short a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…RP33 thus represents a genetically distinct form of adRP and is the first adRP locus assigned to chromosome 2. Taken together with previous reports, and the recent identification of RP31 in 9q (Papaioannou et al 2005), the present study brings the total number of known adRP loci to 17. While the disease genes for 15 of these loci have been identified, RP31 and RP33 remain to be identified by positional cloning.…”
Section: Discussionsupporting
confidence: 61%
“…RP33 thus represents a genetically distinct form of adRP and is the first adRP locus assigned to chromosome 2. Taken together with previous reports, and the recent identification of RP31 in 9q (Papaioannou et al 2005), the present study brings the total number of known adRP loci to 17. While the disease genes for 15 of these loci have been identified, RP31 and RP33 remain to be identified by positional cloning.…”
Section: Discussionsupporting
confidence: 61%
“…30 Several studies have identified mutations in the TOPORS gene that cause dominant RP. 31,32 TOPORS is a cilia-centrosomal protein that localizes to the basal bodies of connecting cilium and to the centrosomes of cultured cells. Morpholino-mediated silencing of topors in zebrafish embryos demonstrated defective retinal development and failure to form outer segments.…”
Section: Discussionmentioning
confidence: 99%
“…58 Linkage mapping continues to locate new adRP genes-most recently RP31 and RP33. 59,60 Likewise, new recessive and X-linked genes are reported regularly. 1 It is impossible to predict whether there are several or many more RP genes that have yet to be discov-ered.…”
Section: Genes and Mutations Causing Adrpmentioning
confidence: 95%